Evaluation of Some Biochemical parameters in Clinically Normal lactating and Ovine Mastitis: 1Jassim M. S. AL-Jubory and 2AL-Hadithy H. AH. - AH., AL-Hadithy H. (The Iraqi Journal of Veterinary Medicine, 2014)
The aim of the present work was to determine the serum iron, total iron binding capacity (TIBC), unbound iron binding capacity (UIBC), transferrin saturation percentage (TS%) and Serum Copper in normal lactating and Ovine mastitis. The study was conducted on 50 clinically normal lactating and 50 ewes affected with staphylococcal mastitis (19 clinical and 31 subclinical), both groups aged 2-5 years in Salah Al-Din governorate. The blood samples were collected from jugular vein during the period October 2012 untill April 2013. The separated sera were directly used for measurement of investigated biochemical tests. The results showed that the ranges and means ± SE of normal lactating and Ovine mastitis were as follows; serum iron 29.81-39. 63µmol /L and 33.38 ± 0.4 µmol /L, 8.76 - 34.11 µmol /L and 20.42 ± 0.98 µmol /L respectively, TIBC 44.7-79.89 µmol /L and 62.03 ±1.65µmol /L, 43.24 - 125.72 µmol /L and 91.24 ± 2.49 µmol /L respectively, UIBC 14.71 - 40.27 µmol /L and 28.57 ± 1.31 µmol /L, 13.41- 113.25 µmol /L and 66.54 ± 3.23µmol /L respectively, TS% 47.92 -71.79 and 55.08 ± 1.01, 14.1 - 65.76 and 26.73 ± 2.71 respectively, and serum copper 13.97 - 23.61 µmol /L and 17.99 ± 0.39µmol /L, 7.1 - 16.09 µmol/L and 11.8 ± 0.32 µmol /L respectively. However, a significant (P<0.05) differences between clinically normal and ewes affected with mastitis were recorded in all the measured parameters.The present data records reference ranges and means ± SE of some biochemical parameters in normal lactating and Ovine mastitis with a significant differences between them.